1987
DOI: 10.1159/000132416
|View full text |Cite
|
Sign up to set email alerts
|

The high-resolution GTG-banding pattern of rabbit chromosomes

Abstract: A cell synchronization technique allowed the high-resolution GTG-banding pattern of rabbit chromosomes to be determined. A karyotype of the late-prophase 622-band stage is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
0
1

Year Published

1991
1991
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 3 publications
2
56
0
1
Order By: Relevance
“…3a. In addition to the three NOR chromosomes (#13, #16 and #20) described previously (Yerle et al, 1987), a clear signal was seen at the tip of the long arm of chromosome 21 (21qter).…”
Section: Chromosomal Localization Of the Rabbit Satellite Dna Familiementioning
confidence: 71%
See 1 more Smart Citation
“…3a. In addition to the three NOR chromosomes (#13, #16 and #20) described previously (Yerle et al, 1987), a clear signal was seen at the tip of the long arm of chromosome 21 (21qter).…”
Section: Chromosomal Localization Of the Rabbit Satellite Dna Familiementioning
confidence: 71%
“…In spite of the fact that rabbit is one of the mammalian species frequently used in the laboratory and biotech industry, its genome, as well as that of the related species, has remained essentially untouched. Although high-resolution GTG-banding of rabbit chromosomes has been described more than a decade ago (Yerle et al, 1987), and recently, chromosome painting studies revealed basic evolutionary relationships within the order (Robinson et al, 2002), apart from a single effort (Ding, 1991), nothing has been published so far on the characterization of the DNA sequence forming the pericentromeric heterochromatin of domestic rabbit (Oryctolagus cuniculus).…”
Section: Introductionmentioning
confidence: 99%
“…As observed previously in the rabbit (Yerle et al, 1987), some bands used as reference landmarks in mid-metaphase were no longer distinct in late prophase and, hence, could not be used as visual references to identify the chromosomes.…”
mentioning
confidence: 84%
“…The banding patterns of rabbit (Oryctolagus cuniculus; 2n = 44) chromosomes have been described in detail: G-banded metaphase chromosomes (Ford et al, 1980 and Committee for Standardized Karyotype of Oryctolagus cuniculus, 1981), G-, Q-and R-banded metaphase chromosomes (Hageltorn and Gustavsson, 1979), G-banded late prophase chromosomes (Yerle et al, 1987) and R-banded prometaphase chromosomes (Poulsen et al, 1988;Rønne et al, 1993;Rønne, 1995). However, the current international nomenclature system for the rabbit karyotype (Committee for Standardized Karyotype of Oryctolagus cuniculus, 1981), providing chromosome and band numbering, is based on G-band patterns only.…”
mentioning
confidence: 99%